A computational approach to predict external spray characteristics for flashing and cavitating nozzles. (September 2018) - Rachakonda, Sampath K.; Wang, Yue; Grover, Ronald O.; Moulai, Maryam; Baldwin, Eli; Zhang, Gaoming; Parrish, Scott; Diwakar, Ramachandra; Kuo, Tang-Wei; Schmidt, David P.
Highlights: Application of Liquid-gas interface area-density model to identity the spray plume boundary in flashing and cavitating nozzles. A detailed explanation of a computational approach to predict external spray characteristics like spray plume angle. The proposed approach offers a meaningful comparison to the experimental definition of spray plume boundary. Model predictions were validated against available experimental results. Abstract: A computational approach to predict external spray characteristics for flashing and cavitating nozzles was presented and validated. It is developed as a fully Eulerian and compressible two-phase flow solver that simulates vaporization and condensation of the fuel using a Homogeneous Relaxation Model (HRM). The flow solver together with the interface area density model was applied to predict spray spreading angle. A method to identify spray plume boundary from the predicted flow field that offers a meaningful comparison to experimental definition was discussed in detail. Using the experimental data available in literature, a comparison between axi-symmetric and asymmetric nozzles was made to assess the nature of the influence of the nozzle geometry and the operating conditions on the ensuing spray. On the basis of this comparison, it was inferred that the spray plume angle of asymmetric nozzles is largely geometry dependent for a wide range of pressure ratios.